Atmospheric concentrations and loadings of organochlorine pesticides and polychlorinated biphenyls in the Canadian Great Lakes Basin (GLB): Spatial and temporal analysis (1992–2012). (October 2016) - Shunthirasingham, Chubashini; Gawor, Anya; Hung, Hayley; Brice, Kenneth A.; Su, Ky; Alexandrou, Nick; Dryfhout-Clark, Helena; Backus, Sean; Sverko, Ed; Shin, Cecilia; Park, Richard; Noronha, Ronald
Abstract: Long-term air monitoring data for POPs are required to determine the effectiveness of source reduction measures and factors controlling air concentrations. Air samples were collected between 1992 and 2012 at three sites with different geographical characteristics (Burnt Island, Egbert and Point Petre) in the Canadian Great Lakes Basin (GLB) using high-volume samplers and analyzed for organochlorine pesticides (OCPs) and polychlorinated biphenyls (PCBs). Spatial and temporal trends of gas-phase concentrations of OCPs, selected PCB congeners and ƩPCBs (84 congeners) were assessed. Egbert had the highest concentrations of some OCPs due to historical [dichlorodiphenyltrichloroethanes (DDTs), dieldrin, γ-hexachlorocyclohexane (γ-HCH)] and current (endosulfan) applications of these pesticides in the surrounding agricultural cropland. This shows that agricultural areas are a source of OCPs to the GLB. High o, p' -/ p, p' -DDT ratios were determined and an increasing trend was observed at Point Petre and Burnt Island up to 2004; indicating that the GLB is influenced by dicofol-type DDT sources, which have higher o, p' -/ p, p' -DDT ratios than technical DDT. Atmospheric PCB concentrations at Egbert and Point Petre are higher than those measured at Burnt Island, likely due to urban influence and greater populations. Loadings calculations suggest that the atmosphere is a source of α-endosulfan and p, p' -DDT to the lakes and the opposite is true for p, p' -DDE. Long-term decreasing trends were observed for both OCPs and PCBs; consistent with control measures implemented in North America. Atmospheric PCB concentrations are decreasing relatively slowly, with halflives in the range of 9–39 years. Chlordane, α-endosulfan, β-endosulfan, dieldrin, and DDT-related substances showed halflives in the range of 7–13 years. α-HCH and γ-HCH were decreasing rapidly in air, with halflives of 5 years. Long-term declining trends of PCBs and OCPs suggest that regulatory efforts to reduce emissions to the GLB environment have been effective, but emissions from primary and secondary sources might limit future declines. Graphical abstract: Highlights: Air concentrations of some pesticides were high at a Great Lakes agricultural site. High o, p′ -/ p, p′ -DDT ratios in Great Lakes air may imply dicofol influence. The atmosphere is a source of α-endosulfan and p, p′ -DDT to the Great Lakes. Long-term decreasing trends were observed for both OCPs and PCBs. Atmospheric PCB concentrations are decreasing slower than OCP concentrations. Abstract : 20 years of POP monitoring in Canada's Great Lakes Basin provide trends on atmospheric concentrations and loadings in support of domestic and international chemical control measures.